Peranan public relations influencer terhadap perilaku nasabah dalam menggunakan mobile banking bank syariah indonesia (BSI) - Anita, Dinda Rosmaya (Maliki Interdisciplinary Journal, 2025)
The development of information and communication technology has driven a major transformation in the banking industry, including Islamic banking. Bank Syariah Indonesia (BSI), as the largest Islamic financial institution in Indonesia, strives to meet the needs of the community through its digital service, BSI Mobile. However, the low interest of some customers in utilizing this service presents a challenge that must be addressed through effective communication strategies. This study aims to analyze the role of Public Relations Influencers in customer behavior in using BSI mobile banking. The research method used a descriptive approach by examining the basic concepts of Public Relations (PR), digital PR strategies, and the influence of influencers on consumer perceptions and behavior. The results of the discussion indicate that PR influencers play a significant role in increasing public awareness, trust, and interest in Sharia-based mobile banking services. Through collaboration with credible Muslim influencers, BSI is able to convey messages in a personal and authentic manner, thus encouraging changes in customer behavior from awareness to loyalty to application use. Furthermore, the influencer PR strategy has proven effective in strengthening BSI's image as a modern Islamic financial institution that adapts to technological developments. This research provides theoretical implications for strengthening the concept of two-way communication (two-step flow of communication) in the context of digital PR, as well as practical implications for BSI in designing a sustainable communication strategy based on Islamic values.